Essentials of negotiation - Lewicki, Roy J.; Barry, Bruce , 1958-; Saunders, David M. (McGraw-Hill/Irwin, 2011)
Explores the major concepts and theories of the psychology of bargaining and negotiation, and the dynamics of interpersonal and inter-group conflict and its resolution